Penyuluh Tentang Bahaya Narkoba Pada Remaja Desa Jebak - Mahdayeni; Zilawati; Windy Elisabet; Chatib Quzwain; Zainatun; Budiman (Jurnal Pelita Pengabdian Masyarakat, 2024)
Adolescence is a transition period where the general problem is the search for identity. Therefore, it often has the urge to present itself as a separate group. However, this encouragement often leads teenagers to serious problems, one of which is drug use. The prevalence rate of drug abuse in special households is much higher than in general households. This indicates that drug abuse and trafficking has its own pockets in society. The level of drug knowledge among people who know the dangers of drugs is quite good, but their understanding of drug prevention efforts is still low. Thus, it is necessary to make maximum communication, education and information efforts, especially in the aspect of strengthening topics or issues regarding how to effectively prevent the threat of the dangers of drugs. In the city of Jambi, there are relatively few drug users among teenagers, namely 29 people in the 10 - 14 year age group and 39 people in the 15 - 18 year age group. Almost all of the teenage drug users live in the working area of ​​the Tahtul Yemen Health Center, namely 27 people in the 10 - 14 year age group and 38 people in the 15 - 18 year age group. Keyword : adolescence, drug abuse, education